Determination of Factors Influencing Dividend Policy: A Case Study of a Manufacturing Company in Indonesia - Vebry Vetarany; Norma Fuji Andini; Putri Puspita Ayu (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the influence of the board of directors, independent board of commissioners, managerial ownership, institutional ownership, profitability, and leverage on dividend policy. This study uses a quantitative research approach and the data used in this study are secondary data obtained from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample of this study is a manufacturing company listed on the Indonesia Stock Exchange in 2019-2022 which was selected by the purposive sampling method so that 66 sample data were obtained. Data analysis techniques are performed using descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that independent board of commissioners and managerial ownership have a positive effect on dividend policy, while profitability and leverage have a negative effect on dividend policy. However, the board of directors and institutional ownership have no effect on dividend policy.